The Reality of Media Training Programs for Palestinian Female Journalists in Light of Digital Media - Al Turk, Ahmed Oraby Hussein (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to reveal the reality of media training for Palestinian female journalists in the Gaza governorates in light of developments in digital media, to identify the nature of professional training that meets their needs, and to evaluate the effectiveness of the training programs provided to them from their own perspective. Methodology: The study relied on the descriptive method, using a survey approach. A questionnaire was applied to a random sample of (80) Palestinian female journalists working in media institutions in the Gaza governorates. Results: The results showed that the most prominent obstacles facing media training were reliance on traditional methods (72.5%), similarity of training topics (63%), and weak funding (52.5%). Additionally, (45%) of respondents indicated the scarcity of specialized training departments within media institutions, (35%) stated that training lacks integration between theory and practice, and (33.75%) pointed to the failure to keep up with technological developments as one of the most significant challenges limiting the success of media training. Conclusion: The study reveals a clear gap between the requirements of professional development for Palestinian female journalists and the reality of the training programs provided to them. This calls for updating methods, diversifying topics, and strengthening the practical and technological aspects of media training to ensure its effectiveness and responsiveness to field needs.